Design Of Single And Dual-Axis Solar Tracker System Using Neural Network - Ngo, Hea Choon; Hashim, Ummi Rabaah; Raja Ikram, Raja Rina; Salahuddin, Lizawati; Cheong, Han Jie (World Academy of Research in Science and Engineering, 2020)
Nowadays, solar energy is becoming more popular as it promotes awareness of an eco-friendly lifestyle. However, solar power generation is insufficient as the primary power generation in Malaysia. To overcome this issue, many private companies are devoting themselves to research to increase the amount of electricity produced by solar panels. Research has shown that a surface perpendicular to direct sunlight increases power generation significantly. Therefore, positioning the solar panel perpendicular to the direct sunlight is crucial as there are many factors to be considered. We will study the difference in dimensional movement and the method of tracking sunlight to make solar panels more efficient in power generation. Light can come from omnidirectional, the movement of the robot must have a higher dimension. Finding the highest intensity of sunlight becomes a challenges because sunlight does not constantly stagnate in a particular location. Therefore, a static solar panel is not as useful as a dynamic solar panel. Besides, the positioning of the sun will change accordingly based on the season. Hence, we need a dynamic solar tracker that can changes its solar panel position as the sun rises or falls. A neural network is chosen as the method of positioning the solar panel by moving with single-axis and moving with dual-axis.